Effectiveness of Cold Compress on Pain Management in Patients with Superficial Burn Injury: A Systematic Review - Dwi Puji Lestari; Lisa Isdaryanti; Luh Gede Wirani Riskayanti Darmawan; I Made Dwi Budhiasa Ari Serengga; Kiki Fajar Nurhidayah; Herdina Mariyanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Superficial burns often cause acute pain that interferes with patient comfort. One of the non-pharmacological methods used to reduce pain is cold compresses, but scientific evidence regarding their effectiveness is still mixed. To evaluate the effectiveness of cold compresses in reducing pain in patients with superficial burns. This systematic review was conducted by searching articles from the Scopus, PubMed, and ScienceDirect databases using the keywords: